Homeless people's perception about the social determinants of health - Maria Caroline das Chagas Winkelmann; Priscila Roberta Lopes; Ivonete Teresinha Schülter Buss Heidemann; Gisele Cristina Manfrini Fernandes; Indiara Sartori Dalmolin (Universidade Federal de Santa Maria, 2018)
Aim: to know the perception of homeless people about the social determinants of health. Method: descriptive study with a qualitative approach, carried by means of semistructured interviews, with 15 homeless people from Southern Brazil, in 2016. The data were analyzed based on thematic analysis. Results: the homeless participants abandoned family life and their homes because of conflictive situations; by the use of licit and illicit drugs; unemployment; and the search for freedom. The family bond is fragile, with little or no contact with the nuclear and extended family. Conclusions: the perception of the social determinants of the homeless people results from the environment in which they live. This highlights the urgent need to strengthen public policies so that this population gains the right to health and changes its living conditions.